Perancangan dan Implementasi Sistem Smart Waste Bin Berbasis ESP32 dengan Integrasi Multi-Sensor - Muhammad Aris; Nehemia Fernando Danamik; Kelvin Adventino Purba; David Rio Manalu; Dian Putra Saragi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The increasing volume of waste has become a serious problem, as conventional waste management systems are still inefficient. This study aims to design a smart waste bin based on ESP32 with multi-sensor integration to improve efficiency.The system uses ultrasonic, infrared, MQ-2, and DHT11 sensors, with a servo as the actuator and a buzzer as an indicator. The results show that the system works well, is responsive, and improves waste condition monitoring.This system provides a practical solution to support environmental cleanliness.